KARAKTERISTIK PENDERITA ASMA BRONKIAL RAWAT INAP DI RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PEKANBARU TAHUN 2011-2013 - Melyana Melyana; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Bronchial asthma is a chronic inflammatory disease (inflammation) in airways characterized by episodic wheezing, coughing, and tightness in the chest due to airway obstruction, included into a group of chronic respiratory disease. Basic Health Research 2013 reports Asthma prevalence in Indonesia is 4.5%. This research is a descriptive study using case series design. The purpose of the research is to determine the characteristics of bronchial asthma patients who are hospitalized in Arifin Achmad Hospital Pekanbaru in 2011-2013. The population of this research is the total number of Bronchial Asthma patients who are hospitalized in Arifin Achmad Hospital Pekanbaru in 2011-2013 which is 237 cases. Data were obtained from medical records (secondary data). The highest proportion of Bronchial Asthma patients are in the age group >45 years (37.6%), female (62.9%), Moslem (93.3%), occupation housewives (38.4%), senior high school education (25.7%), married (64.1%), lives in Pekanbaru (75.5%), non-allergen trigger factors (86.9%), have a family history (56.1%), average length of stay 3.9 days (4 days), not their own source of charge (69.6%), and clinical recovery out patient (89.5%). There is a significant difference between the resource of charge based on the condition when go home (p = 0.003). There was no difference in the average length of stay based on the condition when go home (p = 0.301). There was no difference in the average length of stay based on the resource of charge (p = 0.089). There were no differences in the origin area based on the condition when go home (p = 0.582). The hospital is expected to suggest an allergy test for Bronchial asthma patients to ensure Asthma trigger factors and provide room for the evaluation of patients with Bronchial Asthma. Bronchial Asthma sufferers are expected to always control the disease and avoid the trigger factors of Asthma.